The relationship between leg strength-jump performance and running economy in high school aged long-distance runners - Asano, K.; Goto, Y.; Liu, J.; Uchimaru, J. (The Journal of Strength and Conditioning Research, 2021)
Intorduction: It is well known that not only aerobic capacity, but also leg muscular strength and jump performance as power may contribute to improve running economy. However, studies of the relationship between leg muscular strength and/or jump performance and running economy in high school runners are limited, and clarifying these relationship could be useful for designing training program for high school runners. Purpose: The purpose of this study was to examine the relationship between leg strength and/or jump performance and running economy in high school aged long-distance runners. Methods: 24 high school aged long-distance runners (Age: 16.4 ± 1.1 years; Body Mass: 55.8 ± 4.5 kg; Vo2max: 66.7 ± 3.4 ml/kg/min) participated in this study. This study was approved by Sendai University IRB. Prior to the experiment, since subjects were minors, written consent was obtained from each subject's guardian. All subjects performed jump performance test (4 jumps, drop jump-reactive strength index (RSI) and height of countermovement jump (CMJ)), muscular strength (knee extension and flexion isometric muscular strength) and sub-maximal incremental treadmill test for measuring running performance. We measured cardiopulmonary response such as VE, Vo2 and HR, running economy and time to exhaustion (TE) as running performance on submaximal and maximal incremental treadmill test. This test consists of 3 submaximal stages (running velocity of 5.5, 4.5, and 3.5 min/km) for 3 minutes at 1% grade and maximal stage with a 1 minute rest between each stage. The last stage started from the same running velocity and grade as the third stage, and gradually increased by 1% grade every minnute until exhaustion. Vo2max and HRmax were determined at the fourth stage. %Vo2max at first through third stages were determined by mean Vo2 at last 1 minute of each different stage divided by Vo2max as running economy. TE was determined at the time when subjects could no longer run at the fourth stage. Pearson correlation coefficients were performed to measure correlativity between jump, muscular strength, and running performance. Results: %Vo2max at first through third stages were 61.1 ± 4.1%, 71.4 ± 4.3%, and 89.5 ± 4.0%, respectively. TE was 342 ± 41 second 4 jumps, drop jump-RSI and height of CMJ were 1.37 ± 0.43 m/ms, 1.24 ± 0.51 m/ms, and 34.5 ± 5.3 cm, respectively. Drop jump-RSI was negatively correlated with each stage of %Vo2max (first: r = -0.573, p < 0.01. Second: r = -0.433, p < 0.05. Third: r = -0.470, p < 0.05), whereas it was positively correlated with TE (r = 0.501, p < 0.05). As muscular strength, knee extension and flexion isometric strength were 45.5 ± 10.0 kg and 24.9 ± 4.2 kg, respectively. Muscular strength was not correlated to any index of running performance. Conclusions: From our results, it was suggested that jump performance had a significant relationship with the running economy and TE in high school runners. Therefore, in addition to endurance training, improvement of muscular strength and power could also be important for young runners as same as elite runners. Practical Applications: Drop jump involves fast hip, knee, and ankle motion simultaneously so that is considered as fast SSC action. Intervention of plyometric drills, including fast SSC action, could be useful for improving running economy and TE in high school aged long-distance runners.